Role of Redox Processes in the Pedogenesis of Hypersaline Tidal Flat Soils on the Brazilian Coast. Issue 5 (9th October 2018) - Sartor, Lucas Resmini; Graham, Robert C.; Ying, Samantha C.; Otero, Xosé Luis; Montes, Célia Regina; Ferreira, Tiago Osório
Abstract : Core Ideas: Iron and Mn movement followed by oxidation impose strong control on soil transformations. Sulfidization is not an active process in hypersaline tidal flat (HTF) soils. Coprecipitation of Mn and ferrihydrite controls the geochemistry of Mn in HTF soil. Hypersaline tidal flats (HTFs) represent transitional ecosystems where the ocean, land, and freshwater meet. These places are globally widespread and their soils are an important environmental component controlling chemical reactions in wetland ecosystems. Here, we present a pedogenic study of two HTFs on the Brazilian coast (northeast and southeast) based on the solid‐phase geochemistry of Fe and Mn and morphological studies. Broken and irregular topographies and strong expression of redoximorphic concentrations (e.g., mottles, nodules, and pore linings) are present throughout the soil profiles. Although lepidocrocite is the most abundant Fe fraction in these soils (more than 50% of all extractions), deeper horizons show pyrite as the main Fe fraction caused by the presence of buried mangrove soils. The more oxidizing conditions in these deeper horizons indicate that pyrite is not stable and is undergoing degradation. Iron released in this process is moving upward and precipitating as Fe oxides in more oxidized portions of the soil profile. Coprecipitation of Mn and ferrihydrite seems to be an important process controlling the geochemistry of Mn in HTFs. Our data indicate that deeper horizons have been transforming, driven mainly by water table oscillation and, consequently, redox processes. This process allows translocation of Mn 2+ and Fe 2+ throughout the soil profile, followed by oxidation and precipitation of Mn 3+/4+ and Fe 3+ oxides in preferential sites.